REVIEW ARTIKEL : ANALISIS KADAR SULFAT, pH, DAN OKSIGEN TERLARUT (DO) SERTA KONDUKTIVITAS SEBAGAI PARAMETER KUALITAS AIR MINUM - Andriana, Nita; Yusuf, Bohari; Arif, Moh.Syaiful (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Drinking water quality is critical to public health. This article reviews studies that evaluated sulfate, pH, conductivity, and dissolved oxygen (DO) levels as key parameters in determining drinking water quality. Various water sources, such as tap water, wells, and bottled water, were analyzed in several studies. Sulfate was measured using the spectrophotometric method with BaCl2 reagent and absorbance was measured at a wavelength of 420 nm, while pH used a digital pH meter, conductivity was measured with a conductometer, and DO was measured with the Winkler method. The results showed significant variations in sulfate and dissolved oxygen levels between water sources. Some samples had pH that was below the standard, while sulfate levels in some samples were close to the maximum limit allowed by Permenkes No.492/MENKES/PER/IV/2010 (250 mg/L) and Permenkes No. 32/2017 (400 mg/L). DO proved to be the most sensitive parameter in detecting changes in water quality, followed by pH, and conductivity plays an important role in assessing drinking water quality as it provides an early indication of the concentration of dissolved ions that could indicate contamination, while sulfate is more effective in detecting certain contamination. The combination of these four parameters is important to ensure safe drinking water. This article is expected to guide research and assist water providers in maintaining drinking water quality standards. Keywords : Conduktivity, Drinking Water Quality, Dissolved Oxygen (DO), pH , Sulfate